Burrowing crickets endemic to summits in Mauritius (Orthoptera, Gryllidae): occupation of similar niches by species possibly derived from Australasian and African colonists - Hugel, Sylvain (Zootaxa, 2014)
Two ground burrowing crickets are described from the oceanic island of Mauritius (South Western Indian Ocean): Gialaia (Eugialaia) strasbergi n. sp. belongs to a subgenus that was only known from Papua-New Guinea, and Taciturna baiderae n.sp. belongs to a genus that was only known from South Africa. Taciturna baiderae n. sp. displays a maternal care behavior to clutch of eggs and offspring. Elements of the biology of these two new species are given and their conservation status is assessed.